Building and Evaluating a Green and Multifunctional Composite Based on Poly(butylene adipate-co terephthalate) with Zirconium Phosphate and Clove Essential Oil - Araújo, A. M. C. F.; Freitas, D. F. S.; Souza, Y. C. A.; Albitres, G. A. V.; Garcia, E. E.; Cestari, S. P.; Miguel, M. A. L.; Mendes, L. C. (European Journal of Applied Sciences, 2024)
Although poly(butylene-adipate-terephthalate) (PBAT) is derived from fossil sources, it is classified as a biodegradable polymer because of its predominantly aliphatic ester structure. Synthetic Zirconium phosphate (ZrP) has been widely studied for its notable properties in various fields of human activity. Clove oil (CO) is an eco-friendly material with notable antioxidant and antimicrobial properties. In this context, the present study aimed to develop a green and multifunctional composite based on PBAT incorporated with ZrP, modified ZrP, and CO. The wide-angle X-ray diffraction revealed that the presence of CO promoted the delamination of the phosphates. The thermogravimetric analysis indicated that ZrP and modified ZrP slightly improved the thermal stability of PBAT. The calorimetric evaluations revealed that both ZrP and modified ZrP acted as heterogeneous nucleating agents, increasing the degree of crystallization of PBAT by approximately 70–85%. The incorporation of phosphates and clove oil enhanced the hydrophobicity of the composite films by 20–50%. The thermomechanical analysis indicated a reduction in the glass transition temperature of PBAT and an increase in its linear coefficient of thermal expansion. The type of phosphate and the amount of clove oil influenced the polymer’s molecular relaxation behavior. Antimicrobial testing confirmed that the composite effectively inhibited the growth of Gram-positive bacteria (Staphylococcus aureus and Bacillus cereus) ands the yeast Candida albicans.